2017
DOI: 10.1039/c7ra02212c
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cl2 sensing characteristics of reduced graphene oxide when decorated with copper phthalocyanine nanoflowers

Abstract: A novel gas sensing platform involving a hybrid of reduced graphene oxide (rGO) sheets with unsubstituted copper phthalocyanine (CuPc) nanoflowers has been explored as a room temperature ppb level chemiresistive chlorine (Cl2) sensor with a detection limit as low as 1.97 ppb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 55 publications
(56 reference statements)
3
18
0
Order By: Relevance
“…The very weak absorption peaks at 1627 cm −1 corresponding to the C=C group suggest the presence of organic materials in the samples used as binders 41 . The absorption peaks seen at 1237 and 1737 cm −1 for the green pigment of sample A are consistent with the C–N and N–H stretching modes of copper phthalocyanine 42,43 . Altogether, these FTIR results are consistent with our findings from Raman spectroscopy.
Figure 7Fourier transform infrared (FTIR) spectra for selected pigments present in Jama-Coaque pottery.
…”
Section: Resultssupporting
confidence: 71%
“…The very weak absorption peaks at 1627 cm −1 corresponding to the C=C group suggest the presence of organic materials in the samples used as binders 41 . The absorption peaks seen at 1237 and 1737 cm −1 for the green pigment of sample A are consistent with the C–N and N–H stretching modes of copper phthalocyanine 42,43 . Altogether, these FTIR results are consistent with our findings from Raman spectroscopy.
Figure 7Fourier transform infrared (FTIR) spectra for selected pigments present in Jama-Coaque pottery.
…”
Section: Resultssupporting
confidence: 71%
“…A selective room temperature chemiresistor with a ppb limit of detection for Cl 2 was fabricated through the functionalization of rGO with CuPc nanoflowers ( Figure 6 a). 23 Functionalization of rGO was carried out by mixing CuPc powder and GO in DMF, followed by hydrazine reduction. Structural and spectroscopic studies revealed that CuPc islands grow uniformly in a network of nanoflowers lying parallel to the rGO surface.…”
Section: Hybrids Based On Reduced Graphene Oxide/metallophthalocyaninmentioning
confidence: 99%
“…(c) Conductance–time plots for different doses of Cl 2 . Adapted with permission from ref ( 23 ). Copyright 2017, Royal Society of Chemistry.…”
Section: Hybrids Based On Reduced Graphene Oxide/metallophthalocyaninmentioning
confidence: 99%
“…The sensor detection limit was measured to be 1.97 ppb at room temperature. (80) The physisorption of Cl 2 molecules occurred on the central metal ion present on the grains of CuPc-decorated rGO. Table 1 shows the sensing responses of several graphene-based gas sensors for some toxic gases.…”
Section: Detection Of Toxic Gasesmentioning
confidence: 99%